Perancangan Sistem Informasi Reservasi Berbasis Web Menggunakan Framework Codeigniter di SEI Hotel Banda Aceh - Darwati, Dedek Susi (Yayasan Kawanad, 2024)
Guest reservation information system represents a digitalization solution for room booking processes at SEI Hotel Banda Aceh aimed at improving hotel operational efficiency. This research aims to design and implement a web-based reservation information system using CodeIgniter framework with HTML, PHP, CSS, JSON, AJAX technologies, and MySQL database. The research methodology employs a waterfall approach encompassing analysis, design, coding, testing, and maintenance phases. Data collection was conducted through literature study and field observation with direct interview techniques to hotel staff. Research results demonstrate that the developed system successfully addresses manual recording problems previously encountered by the hotel. The new system provides online room booking features, guest data management, room availability management, and automatic report generation. System advantages include increased reservation process speed, ease of data retrieval, information security through user authentication systems, and reduced recording error risks. Web-based system implementation enables unlimited time and location access, thereby enhancing service quality for prospective guests. The system has been tested and proven to significantly improve hotel reservation management effectiveness.